2002
DOI: 10.1002/cncr.10344
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pretreatment risk factors and Ga‐67 scintigraphy early during treatment for prediction of outcome of patients with aggressive non‐Hodgkin lymphoma

Abstract: BACKGROUNDClinical pretreatment risk factors indicate the severity of disease in patients with aggressive non‐Hodgkin lymphoma (NHL). Ga‐67 scintigraphy during treatment is an early indicator of treatment‐related features of lymphoma cells. The ability of risk factors and Ga‐67 to predict disease outcome was compared in 139 patients with aggressive NHL.METHODSPretreatment clinical risk factors and Ga‐67 scintigraphy performed after one cycle and at mid‐treatment were evaluated for their correlation with respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This finding has not been previously reported and should be confirmed in larger series. The subtype of GS false negatives was not indicated in the series reported by Israel et al [9]. Regarding FDG, false negatives were only detailed in the paper by Spaepen et al [13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding has not been previously reported and should be confirmed in larger series. The subtype of GS false negatives was not indicated in the series reported by Israel et al [9]. Regarding FDG, false negatives were only detailed in the paper by Spaepen et al [13].…”
Section: Discussionmentioning
confidence: 96%
“…The early response to chemotherapy is strongly associated with long-term outcome [8]. GS performed after one [9] or two cycles of chemotherapy [10] has been proved to accurately predict outcome in patients with aggressive NHL. Similar results were also obtained with FDG-PET performed after one to three cycles of chemotherapy [11 -15].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy percent of patients with negative interim scan remained disease free, whereas only 25% of gallium-positive patients at the same therapeutic point achieved durable remission. More recently, Israel and colleagues 15 confirmed that gallium after 1 cycle was the most significant predictor of patient outcome, compared with pretreatment risk factors such as performance status, stage, and IPI, in 57 patients with aggressive lymphoma. Unfortunately, gallium scintigraphy is limited by its low sensitivity and by poor spatial resolution of ␥ cameras.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas some authors [16,27] found no differences between these two groups of patients, others [23,28] have reported that patients transplanted with measurable disease at ASCT have a worse outcome. In this sense, 67 Ga scan has successfully been used for many years for this purpose in patients with lymphoma after standard chemotherapy [29][30].…”
Section: Discussionmentioning
confidence: 99%